Antioxidant Activity of the Herbal Combination of Black Cumin (Nigella sativa L.) with Soursop Leaves (Annona muricata L.) OR Celery (Apium graveolens L.) - Wardatun, Sri; Sofihidayat, Trirakhma; Noorlaela, Ella; Agustin, Vina (Universitas Muhammadiyah Surakarta, 2024)
Excessive free radicals in the body can cause various degenerative diseases; antioxidants can reduce the impact of free radical injury. Several plants have been tested for antioxidant activity, including black cumin (Nigella sativa L.), soursop leaves (Annona muricata L.), and celery (Apium graveolens L.). Black cumin is easy to find in several finished products on the market in Indonesia alone or in combination with other ingredients, including soursop leaves and celery. This study aimed to explore the interaction of laboratory-prepared and commercial combinations of black cumin extract with soursop or celery extract. The antioxidant activity of each extract was determined, and the combined antioxidant activity was calculated. The interactions of the combinations were identified based on the interaction factor values. The antioxidant activities were measured using DPPH (2,2-diphenyl-1-picrylhydrazyl) reagent. The results revealed nearly all exhibited strong antioxidant activity, except for black cumin–based commercial combination preparations, which demonstrated weak had antioxidant activity. Moreover, all combination extracts—laboratory made or commercial—had an IF value of 1. Conclusion: The combination of black cumin extract with soursop or celery leaf extract resulted in an antagonistic effect (IF 1) on the antioxidant ability.